STRATEGIC OVERTIME IMPLEMENTATION: ASSESSING CRASH TIME, CRASH COST, AND COST SLOPE IN THE CONSTRUCTION OF KADIRI UNIVERSITY'S 4-STORY BUILDING - Ali, Mahardi Kamalika Khusna; Tjendani, Hanie Teki; Witjaksana, Budi (International Journal Science and Technology, 2024)
The lecture building is an important building which is the center of academic activities where educational activities are carried out. Currently, the construction of a four-story lecture building at Kadiri University is experiencing significant project delays with a deviation of 5.64% from the plan. Crash analysis can be carried out to speed up the duration of the project so that it can be completed on time with additional working hours. This research aims to determine crash time, crash costs, and cost slope for the application of overtime on the 4-story building construction project at Kadiri University. A quantitative and case study approach was used with data collected through observation, interviews, and analysis of project documents. Critical Path Method (CPM) analysis is carried out using Microsoft Project software to identify work that is on the critical path. Crashing is done by calculating crash time, crash cost, and cost slope. The research results show that applying 1 hour of overtime can speed up the project by 12 working days, with an additional cost of IDR 24,488,758. Cost slope analysis shows additional overtime costs of IDR 12,244,379. This research shows that the application of measurable overtime and crashing analysis can effectively overcome project delays in the context of building educational facilities.